2015
DOI: 10.1016/j.crad.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving malignancy prediction in breast lesions with the combination of apparent diffusion coefficient and dynamic contrast-enhanced kinetic descriptors

Abstract: The best malignancy predictors were low ADCs and washout curves. ADC and kinetic parameters provide differentiated information on the microenvironment of the lesion, with joint models displaying improved predictive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…Breast cancer is a heterogeneous tumor with different molecular patterns and remains the second leading cause of cancerrelated death after lung cancer. [1][2][3] In recent years, besides the ultrasound and mammography, breast MRI has become a widespread modality in the diagnosis of breast cancer. Dynamic contrast-enhanced MRI yields information about enhancement of the lesion by using kinetic curves to differentiate benign lesions from malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Breast cancer is a heterogeneous tumor with different molecular patterns and remains the second leading cause of cancerrelated death after lung cancer. [1][2][3] In recent years, besides the ultrasound and mammography, breast MRI has become a widespread modality in the diagnosis of breast cancer. Dynamic contrast-enhanced MRI yields information about enhancement of the lesion by using kinetic curves to differentiate benign lesions from malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging is sensitive to biophysical characteristics of tissues and affected by tissue cellularity, edema, and necrosis. 2,3,[18][19][20] The majority of the studies performed up to the present indicated that lower ADC values with the variable ADC cutoff values were significantly associated with malignancy. 2,3,10,14,[18][19][20] And also some previous studies revealed that combined analysis of DCE-MRI and DWI had a potential role in the detection of malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations